Behavior of eccentrically loaded circular CFRP-steel composite tubed steel-reinforced high-strength concrete columns. (July 2020) - Yang, Junlong; Wang, Jizhong; Zhang, Shuo; Wang, Ziru
Abstract: This paper investigates the behavior of circular CFRP-steel composite tubed steel-reinforced high-strength concrete columns under eccentric compression. The failure modes and load versus mid-span lateral displacement curves were analyzed comprehensively for the specimens with different test parameters. The experimental results show that the different continuities of the external steel tube has a great impact on failure patterns. The crushing of concrete and bulging of the steel tube in the compression side occurred near the 1/4 height of the specimens with grooves at 25 mm away from the end plates on the external tube, while, for the specimens with no gaps on the steel tube, local buckling was observed around the mid-height of the columns. However, the extent of bulging can be significantly alleviated with the increase of CFRP layers. Finite element (FE) analysis was conducted by using ABAQUS software in this study and the results show that good agreement can be achieved between the test observations and FE results. Based on the valid FE model, the parametric analysis was performed and a new model was proposed to predict the axial-flexural interaction behavior of the composite columns. It is evident that the theoretical predictions agree well with the FE results of the specimens in this paper with a certain safety margin (approximately 15%), which may provide a valuable guideline for the engineering design of CFRP-steel composite tubed steel-reinforced high-strength concrete columns. Highlights: Eccentrically compressive behavior of CFRP-steel composite tubed columns was investigated by the experimental program. A valid finite element model was developed for the tested specimens. A new model in predicting the axial-flexural interaction behavior of CFRP-steel composite tubed columns was proposed.